2012
DOI: 10.1103/physreva.86.043835
|View full text |Cite
|
Sign up to set email alerts
|

Probing the dynamical behavior of surface dipoles through energy-absorption interferometry

Abstract: Spatial interferometry, based on the measurement of total absorbed power, can be used to determine the state of coherence of the electromagnetic field to which any energy-absorbing structure is sensitive. The measured coherence tensor can be diagonalized to give the amplitude, phase, polarization patterns, and responsivities of the individual electromagnetic modes through which the structure can absorb energy. Because the electromagnetic modes are intimately related to dynamical modes of the system, informatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…The EAI technique relies on using two identical source probes to map correlations of the detector beam; therefore, we will consider the field produced by two such sources as described by (6). If two such identical sources are positioned at indices m and m , the resulting optical field produced by both sources can be expressed as e m,m = e m + e m exp (iφ) (7) where φ is an intrinsic phase difference between the two sources.…”
Section: Matrix Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…The EAI technique relies on using two identical source probes to map correlations of the detector beam; therefore, we will consider the field produced by two such sources as described by (6). If two such identical sources are positioned at indices m and m , the resulting optical field produced by both sources can be expressed as e m,m = e m + e m exp (iφ) (7) where φ is an intrinsic phase difference between the two sources.…”
Section: Matrix Representationmentioning
confidence: 99%
“…In this work, we applied energy absorption interferometry (EAI), which is a general technique by which the coherent properties of any power-absorbing structure can be measured, to an end-to-end THz optical system including detectors [7]. In doing so, we demonstrated that we were able to recover a complex-valued correlation matrix, which described the sensitivity of the system to individually coherent natural modes.…”
mentioning
confidence: 99%
“…Energy Absorption Interferometry (EAI) is a technique that was originally proposed for detector characterisation [6], and has recently been demonstrated experimentally in this context [8]. More recently, its use as a general tool for characterising power absorption in structures has been studied [12]. As illustrated in Fig.…”
Section: Power Absorbed By a Periodic 2d Surfacementioning
confidence: 99%
“…where sum and difference coordinates have been used in both spatial and spectral domains. Regarding the latter, in order to simplify the notation, we have mixed (k y1 , k y2 ) coordinates (and related (k z1 , k z2 ) wavenumbers) with (k + , k − ) coordinates, with the link between variables given by (12). In this section, the periodicity of the structure is introduced by noticing that the correlation function is periodic versus the sum coordinate r = (y 1 + y 2 )/2.…”
Section: Characterization Through Energy Absorption Interferometrymentioning
confidence: 99%
“…In this paper, we propose the use of a technique called Energy-Absorption Interferometry (EAI), 2,3 to fully characterize the optical behavior of near-infrared detectors. Saklatvala and Withington 4 have previously shown that a detector's optical behavior can be fully parametrized using a two-point response dyadic.…”
Section: Introductionmentioning
confidence: 99%